Rosalie and other love songs - Saidah Rastam (Strategic Information and Research Development Centre, 2017)
Beautiful music, born from an eclectic mix of cultures, was created in Malaya in the period leading up to country's independence in 1957. But this cultural history has yet to be told now. Saidah Rastam draws in extensive interviews with those who made that history, corroborating and elaborating this testimony by trawling songs and scores films. As a point of entry into this fascinating story, she explores the controversies surrounding the provenance of Malaysia's national anthem, 'Negara Ku', and embroiders a kind of detective story, drawing the reader into broader, contextual issues to do with culture, politics and society. The result is an innovative and perceptive account: well researched, splendidly constructed, deeply knowledgeable, beautifully illustrated and stylishly written in a way that captures the very musicality of its topic. The first edition of Rosalie and Other Love Songs was enthusiastically received, and this new, revised edition will be welcomed by all those with an interest in Malaysian culture and history, as well as fans of popular music worldwide. 'Rosalie and Other Love Songs begins with a mystery about a love song and stealthily, turns into a history of Malaya as a time, as frame of mind, as nation. There is no other book like it on our country.' - Kathy Rowland, ArtsEquator 'Written with passion and clarity, exhaustively researched and lavishly illustrated, this enlightening and inspiring book will resonate with all Malaysians. Through the timeless songs that Saidah Rastam describes, we are masterfully guided on a voyage to our past that, ultimately, also charts a map for our future. Rosalie and Other Love Songs is a timely reminder to us that the history of our country is composed of countless strands, with each strand bound to the other, creating a unique and delicate tapestry to be cherished and preserved.' - Tan Twan Eng, author